Portal hemodynamic effects of lenvatinib in patients with advanced hepatocellular carcinoma: A prospective cohort study. Issue 9 (27th July 2020) - Hidaka, Hisashi; Uojima, Haruki; Nakazawa, Takahide; Shao, Xue; Hara, Yusuke; Iwasaki, Shuichiro; Wada, Naohisa; Kubota, Kosuke; Tanaka, Yoshiaki; Shibuya, Akitaka; Kanoh, Yuhsaku; Kokubu, Shigehiro; et al.
Abstract : Aim: Lenvatinib is an oral, multitargeted, tyrosine kinase inhibitor, which suppress tumor angiogenesis and tumor progression. It was non‐inferior to sorafenib in overall survival in untreated advanced hepatocellular carcinoma (HCC). Sorafenib had a beneficial effect on portocollateral circulation with portal hypertension in translating and clinical studies. However, the hemodynamic effects of lenvatinib appear to be different from those of sorafenib because the efficacy of lenvatinib for vascular endothelial growth factor receptors and fibroblast growth factor receptors is different from that of sorafenib. This study was prospectively performed to evaluate the portal hemodynamic effect of lenvatinib in patients with advanced HCC using duplex Doppler ultrasonography. Methods: In total, 28 Child‐Pugh class A or B patients with advanced HCC received lenvatinib depending on body weight daily for 2 weeks. Primary outcomes were changes in the hemodynamics of the portal venous system using duplex Doppler ultrasonography before and after the 2‐week administration of lenvatinib. Results: The portal venous flow velocity (cm/s) significantly reduced (27 ± 12.1 vs. 22.6 ± 8.0, P  = 0.019), while portal venous area (cm 2 ) did not change after the 2‐week administration (0.80 ± 0.36 vs. 0.82 ± 0.27, P  = 0.665). Therefore, the congestion index (portal venous area/portal venous flow velocity), which reflects the pathophysiological hemodynamics of the portal venous system significantly worsened (0.037 ± 0.025 vs. 0.043 ± 0.024, P  = 0.045). Conclusions: Considering that this was a short‐term study, because lenvatinib could be an agent that aggravates portal hypertension, it will be necessary to verify its clinical effects for portal hypertension in future studies.